UMP, HsMA seal collaboration in Business Engineering Dual Degree programme - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
GERMANY, 3 June 2022 - Universiti Malaysia Pahang (UMP) signed a memorandum of understanding (MoU) with Hochschule Mannheim (HsMA) Germany to implement academic and student staff exchange programmes for both universities.